Staying or moving: Results of a latent transition analysis examining intra-individual stability of recreational substance use among MSM in the Multicenter AIDS Cohort Study from 2004 to 2016. (1st March 2021) - Noor, Syed W.; Hart, Trevor A.; Okafor, Chukwuemeka N.; Ware, Deanna; Chew, Kara W.; D'Souza, Gypsyamber; Ho, Ken; Friedman, M. Reuel; Plankey, Michael
Highlights: Examined change in substance use over a 12-year period among 3568 U. S. MSM. Using LTA investigated transitioning from one class of substance use to another. Alcohol use was the most prevalent followed by marijuana, popper, cocaine, and ED. Overall decline in cocaine, and ED use but an increase in marijuana and heroin. Participants maintained use of the same substance(s) over longer periods of time. Abstract: Background: Studies have examined patterns of substance use among Men who have Sex with Men (MSM), but few have examined factors predicting transitioning from one substance use pattern to another. We investigated transitioning from one substance use pattern to another over a 12-year period (2004–2016) among the Multicenter AIDS Cohort Study participants. Method: Alcohol, marijuana, heroin, cocaine, poppers, uppers (e.g., methamphetamines) and erectile dysfunction(ED) medications use in the last 6 months from 3568 US MSM was dichotomized (no/yes) to classify participants into substance use classes at each follow up visit. We fit latent transition models to calculate transition probabilities of moving from one substance use class to another over a 3, 4 and 6-year time period. Then fit regression models to identify factors associated with the probability of each participant staying in or moving from the same substance use class. Results: Overall, cocaine and ED medication use declined but marijuana and heroin use increased over 2004−2016. We observed most participants (84.6 %–100 %) stayed in the same class. Increased age was associated with transition from the Minimal -use class to the Alcohol-only class (aOR = 1.06, 95 %CI:1.01−1.13; p < 0.01) and non-White MSM reported lower odds of moving from the Alcohol-only class to the Alcohol-Popper class (aOR = 0.50, 95 %CI:0.30−0.82; p <0.01). There were no difference in the transition probabilities by HIV-status. Conclusion: Despite decline in substance use in general, participants are highly stable in their choice of substances. However, treating MSM as a homogeneous group can lead to an under-appreciation of the diversity of prevention needs and treatment of substance using MSM.